Extended and pedicled pectoralis major flap for right orbitofrontal-parietal reconstruction following invasive squamous cell carcinoma resection - Andres Ordenes Evensen; Daniel Cazeto López; Andrés Fernando Cánchica; Carlos Fernando Goyeneche; Leonardo Gobetti; Renato Giannini; Osvaldo Ribeiro Saldanha (Revista Brasileira de Cirurgia Plástica, 2019)
Introduction: The myocutaneous flap is often used in reconstruction of head and neck defects. However, it is restricted to the middle third of the face. Perforating artery dissection techniques allow further lengthening of the pedicle, thus achieving coverage of the orbitofrontal-parietal region. Case report: A 63-year-old male with a poorly-differentiated invasive squamous cell carcinoma presented with a final defect of 12.0 × 18.0 cm in the right orbitofrontal-parietal region, with dura mater, frontal sinus, and right upper orbit exposure after resection. We designed a pectoralis major flap, with a cutaneous island equaling the defect in dimensions, in the right parasternal region, from the fourth intercostal space to the subcostal region (extended). The pedicle was sectioned after 4 weeks. The coverage was effective, with no major complications, and a satisfactory aesthetic result. Conclusion: This flap can be an excellent option for reconstruction of the upper third of the head when there are limitations to microsurgery.